An Inside Job: Engaging with Indigenous Legal Traditions through Stories - Napoleon, Val; Friedland, Hadley (McGill Law Journal, 2016)
There has been a growing momentum toward a greater recognition and explicit use of Indigenous laws in the past several years. According to the Truth and Reconciliation Commission’s final report, the revitalization and recognition of Indigenous laws are essential to reconciliation in Canada. How, then, do we go about doing this? In this article, we introduce one method, which we believe has great potential for working respectfully and productively with Indigenous laws today. We engage with Indigenous legal traditions by carefully and consciously applying adapted common law tools, such as legal analysis and synthesis, to existing and often publicly available Indigenous resources: stories, narratives, and oral histories. By bringing common pedagogical approaches from many Indigenous legal traditions together with standard common law legal education, we hope to help people learn Indigenous laws from an internal point of view. We share experiences that reveal that this method holds great potential as a pedagogical bridge “into” respectful engagement with Indigenous laws and legal thought, within and across Indigenous, academic, and professional communities. In conclusion, we argue that, while this method is a useful tool, it is not intended to supplant existing learning and teaching methods, but rather to supplement them. In practice, we have seen that this method can be complementary to learning deeply through other means. There are many methods to engage with Indigenous laws, and there needs to be critical reflection and conversations about them all.